COVID-19's Impact on Museums in the Digital Era: Evidence from Hong Kong - Dr. Khanadel-wil; Dr. Li Wang (Al-Qanṭara, 2023)
Due to restrictions on running customary exhibitions and curatorial programmes, museums—as sites of public meeting for locals—have encountered unprecedented difficulties during the coronavirus illness 2019 (COVID-19) epidemic. As a response, museums undertook equivalent emergency measures to speed the creation of the infrastructure for digital resource and service platforms. These difficulties brought up a number of possible problems, such as the usage of electronic materials and a discrepancy between visitor expectations and museum services. This study examines the problems that Hong Kong museums face in light of COVID-19, as well as the emergency procedures, intentional practises, and effects of COVID-19 on the roles and duties of Hong Kong museums from the viewpoints of museum staff and visitors. Numerous online interactions and offline upgrades were found, however visitor